UTILIZATION OF DIETHANOLAMIDE SURFACTANT FROM METHYL ESTERS OF PALM OIL IN HERBICIDE FORMULATION WITH ACTIVE ISOPROPYLAMINE GLYPHOSATE - Rusdiana, Ika Agustin; Hambali, Erliza; Rahayuningsih, Mulyorini (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2020)
A surfactant that can be developed from palm oil is non-ionic. Diethanolamine is a nonionic surfactant based on palm oil methyl ester, which can replace the use of polyoxyethylene amine surfactant in a commercial herbicide formula that harms the environment. This research aimed to determine the physicochemical properties of diethanolamine surfactant and to study the effect of diethanolamine surfactant addition in herbicide formulation with active ingredients of isopropylamine glyphosate. This study was arranged in a complete randomized design with surfactant concentrations as treatment, consisting of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 4%, 5%, 6%, 7%, 8%, and 9% (w/w). The results showed that there was a significant effect of diethanolamine surfactant addition on the characteristics of the herbicide formulation. The concentration of 5% diethanolamine surfactant had the best character in producing herbicide with the lowest surface tension and a contact angle of 30.73 dyne/cm and 11.48°. The commercial herbicide, having a surface tension of 36.27 dyne/cm and a larger contact angle of 83.03°, was used as the comparison for the formulations. The stability of the solution was up to 100% for 5 weeks at room temperature with solubility in water of 80.60% and droplet size of 7.20 ?m.